The End of Language Policy? English, Capital, and Multilingual Elites in China's Transnational Higher Education - Zhu, Honghui (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2026)
This thesis investigates language policy in China's transnational higher education, i.e., Sino-foreign education. It examines how English, Chinese, and other languages are used, perceived, and managed among three Sino-foreign institutions of varying prestige. The study combines theories from language policy in multilingual contexts and the Marxian materialist view, and adopts a qualitative-driven mixed methods approach, linking everyday classroom language practices with economic, cultural or ideological aspects that are crucial to Sino-foreign education. The thesis includes seven chapters. Chapter 1 outlines the rationale and aims of the study, focusing on language practices in Sino-foreign universities as part of China's broader engagement with transnational education (TNE). It introduces the epistemological and methodological approach adopted in the research and provides an overview of the thesis structure. Chapter 2 provides background on TNE, including definitions, categories, and incentives. It distinguishes transnational from national initiatives and situates China in the global TNE landscape. The chapter traces the development of Sino-foreign education from missionary roots to present collaborations and identifies institutional and organisational features. Further sections review the geographical distribution, financial arrangements, and tuition systems of Sino-foreign institutions. It addresses challenges such as collaboration dilemmas and inequalities. Chapter 2 concludes with an overview of languages in China, including the roles of Putonghua and English in Chinese society and education. Chapter 3 reviews the literature and theoretical foundation. It discusses the historical development of the field of language policy, and key concepts such as language practice, language ideology, and language management and governmentality that are central to the examination. English-medium instruction (EMI) policies, practices, and ideologies in multilingual higher education are reviewed, leading to the problems navigated in the study of language policy. By pointing out the problems of culturalist perspectives and transnational multilingual elites, the chapter proposes the End of Language Policy as a development stage. It then leads to a materialistic class theory of language policy as the study's theoretical basis. Chapter 4 details the research design. It presents the research questions and outlines a qualitative-driven mixed-methods approach informed by dialectical pragmatism. Three institutions were selected for data collection through archival documents, classroom observations, interviews, and a questionnaire. Research ethics approval procedures, positionality, and analytic processes, such as transcription, translation, and thematic analysis are described, supported by systematic triangulation. Chapter 5 reports findings from the three institutions. Archival, observational, and questionnaire data are presented around key themes from theoretical orientations. Interview results are presented according to the thematic categories. Chapter 6 discusses the findings. English and Chinese serve as means of knowledge transfer and meaning-making, forming a hierarchical multilingual order. Teachers and students act as language managers within largely implicit English-dominant policies. The role of capital is linked to EMI, Chinese domestic migration, and elite formation. Cultural and identity dynamics reflect the reasons for Chinese monolingual ideology while acknowledging multicultural reality, with institutional differences framed through wind and viewing as governmentality. Chapter 7 contains a summary of this thesis and it concludes by summarising the findings according to the research questions and discussing their implications for understanding language policy, transnational higher education and broader contexts.
APPROVED
Keywords: language policy; transnational higher education; multilingualism; language ideology; English medium instruction